2014
DOI: 10.3109/02699052.2014.901559
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of post-operative recurrence of chronic subdural haematoma using mean haematoma density

Abstract: This study provides statistical proof that MHD is a significant, independent, prognostic factor for the post-operative recurrence of CSDH. As such, consideration of MHD could aid in the prediction of post-operative prognosis of CSDHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
(33 reference statements)
0
21
1
Order By: Relevance
“…Although there were bilateral hematomas in 26% of our patients (37/140), no higher risk of recurrence was noted, whereas some other authors have described a correlation with a high recurrence rate [15,30].…”
Section: Recurrencecontrasting
confidence: 56%
See 1 more Smart Citation
“…Although there were bilateral hematomas in 26% of our patients (37/140), no higher risk of recurrence was noted, whereas some other authors have described a correlation with a high recurrence rate [15,30].…”
Section: Recurrencecontrasting
confidence: 56%
“…Nagakushi et al reported a correlation between the type of hematoma and cranial base location with a higher risk of recurrence. A higher density on CT scans was also reported as a risk factor for recurrence [14,15,28]. Higher density CSH have been reported to have a greater risk of rebleeding, and high protein exudation rates.…”
Section: Recurrencementioning
confidence: 95%
“…Many studies suggest that preoperative hematoma density is associated with CSDH recurrence, and hyperdense hematoma is an independent risk factor for CSDH recurrence [13,38]. In present study, although nearly 1/3 of the patients had hyperdense imaging findings, according to our clinical experience and our definition of CSDH, neurosurgeons evaluated patients with subdural hematoma no matter what the density of subdural hematoma on imaging, once they were able to be treated with BHD, these patients could be managed as patients with CSDH.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, hematoma density was not significantly associated with postoperative AIH. We suspect that when hyperdense hematoma are compared with the other three types of hematoma density, repeated microhemorrhages from the immature capillary network in the outer membrane take place and accumulate over time, causing CSDH recurrence [38].…”
Section: Discussionmentioning
confidence: 99%
“…Tugcu et al 22 found that bilateral hematoma was correlated with a high recurrence rate. Lin et al 23 discovered that the mean hematoma density, the separated type, and bilateral and skull base involvement of CSDHs were significantly related to postoperative recurrence. Protective factors have also been explored in many studies, including artificial cerebrospinal fluid irrigation 19,24 and postoperative drainage.…”
Section: Discussionmentioning
confidence: 99%